2022
DOI: 10.3390/children9020287
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-National Analysis of the Effects by Bullying and School Exclusion on Subjective Happiness in 10-Year-Old Children

Abstract: Literature to date has well supported the detrimental consequences of bullying and school exclusion in different countries, with negative outcomes in school adjustment or child psychological adjustment, among others. However, more research is needed to understand the effects on positive indicators of psychological well-being in children as subjective happiness. Cross-national studies are also recommended to examine the differential effects by country. Thus, the aim of this study was to examine bullying and sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(34 reference statements)
2
3
0
1
Order By: Relevance
“…The study conducted by Navarro, Ruiz-Oliva, Larrañaga, and Yubero [ 28 ] found that cyberbullying victims informed of the worse levels of subjective well-being than children not involved in cyberbullying. Similar results have been found in subsequent research [ 29 , 30 ].…”
Section: Introductionsupporting
confidence: 93%
“…The study conducted by Navarro, Ruiz-Oliva, Larrañaga, and Yubero [ 28 ] found that cyberbullying victims informed of the worse levels of subjective well-being than children not involved in cyberbullying. Similar results have been found in subsequent research [ 29 , 30 ].…”
Section: Introductionsupporting
confidence: 93%
“…The previous study in Samarinda (Susanti et al, 2018) showed that as many as 51.3% of school children tended to have experienced bullying victims at school. This is supported by other studies (Gomez-baya et al, 2022)that the negative effect of bullying at school is that it will affect the level of happiness of children which can have an impact on the pattern of children's lives at home. So, this is in line with this study that parents make the issue of bullying as one of the health information searches.…”
Section: Figure 1 Frequency Of Parents In Seeking Children's Health I...supporting
confidence: 74%
“…School bullying, considered a common social phenomenon worldwide, can have serious consequences, ranging from physical symptoms to significant psychiatric symptoms such as depression, anxiety, insomnia, self-harm, etc., also including poor academic performance. Likewise, it is also associated with problems in social relationships and impaired quality of life [ 4 , 21 , 22 , 23 , 24 , 25 ]. Physical, verbal and social abuse is a major health problem for students; those who are victims may have poorer emotional, social, academic and health development, while bullies tend to display delinquent and aggressive behaviors in late adolescence [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%